1982
DOI: 10.1139/v82-216
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance of spin-trapped radicals of amines and polyamines. Hydroxyl radical reactions in aqueous solutions and γ-radiolysis in the solid state

Abstract: MAGDI M. MOSSOBA, IONEL ROSENTHAL, and PETER RIESZ. Can. J. Chem. 60, 1493 (1982). The reactions of hydroxyl radicals with methylamine, dimethylamine, trimethylamine, diethylamine, see-butylamine, ethylenediamine, 1,3-diaminopropane, putrescine, cadaverine, 1,7-diaminoheptane, ornithine, spermidine, spermine, agmatine, and arcaine in aqueous solutions have been investigated by spin-trapping and esr. Hydroxyl radicals were generated by the uv photolysis of H,O, and 2-methyl-2-nitrosopropane (MNP) was used as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The redox potential for (NH 2 CHCOO •– /NH 2 CH 2 COO – ) is 0.8 V, and the redox potential for ( + NH 3 CHCOO •– / + NH 3 CH 2 COO – ) is 1.5 V, explaining the pH effect on k 7 . The observation that k 7 for H 2 NC(H 2 /D 2 )CO 2 – is orders of magnitude higher than that for + H 3 NC(H 2 /D 2 )CO 2 – is in accord with the analogous reaction of • OH radicals with glycine and other amino acids and amines. , This points out the effect of the delocalization, reorganization energy of the radical H 2 NC(H/D)CO 2 •– and the effect of the −NH 3 + /NH 2 groups on the bond dissociation energy of + H 3 NC(H 2 /D 2 )CO 2 – /H 2 NC(H 2 /D 2 )CO 2 – on the rate of the HAT.…”
Section: Resultssupporting
confidence: 63%
“…The redox potential for (NH 2 CHCOO •– /NH 2 CH 2 COO – ) is 0.8 V, and the redox potential for ( + NH 3 CHCOO •– / + NH 3 CH 2 COO – ) is 1.5 V, explaining the pH effect on k 7 . The observation that k 7 for H 2 NC(H 2 /D 2 )CO 2 – is orders of magnitude higher than that for + H 3 NC(H 2 /D 2 )CO 2 – is in accord with the analogous reaction of • OH radicals with glycine and other amino acids and amines. , This points out the effect of the delocalization, reorganization energy of the radical H 2 NC(H/D)CO 2 •– and the effect of the −NH 3 + /NH 2 groups on the bond dissociation energy of + H 3 NC(H 2 /D 2 )CO 2 – /H 2 NC(H 2 /D 2 )CO 2 – on the rate of the HAT.…”
Section: Resultssupporting
confidence: 63%
“…The delocalized positive charge increases the electron density on the adjacent δ-CH 2 to a greater extent than on γ-CH 2 and β-CH 2 . 36 Given that • H abstraction by • OH is an electrophilic process, the • OH preferentially reacts with the electron-rich δ-CH 2 . Higher electron density at δ-CH 2 also leads to a higher reaction rate of arginine toward • OH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Under physiological conditions, the guanidyl is protonated, and its charge is delocalized over the guanidyl group. The delocalized positive charge increases the electron density on the adjacent δ-CH 2 to a greater extent than on γ-CH 2 and β-CH 2 . Given that • H abstraction by • OH is an electrophilic process, the • OH preferentially reacts with the electron-rich δ-CH 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the course of an investigation of free radicals derived from polyamines (27) it was found that when a dimethyl sulfoxide solution of MNP (1.5 mglmL) and dibenzoyl peroxide (5 mglmL) was saturated with 1,8-diaminooctane in the dark, at room temperature, the methyl spin adduct spectrum was exclusively observed. Control experiments indicated that all of these components were necessary for the formation of the methyl adduct.…”
Section: Ohmentioning
confidence: 99%